2015
DOI: 10.1155/2015/294024
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Liver Iron Concentration by MRI Is Reproducible

Abstract: Purpose. The objectives were (i) construction of a phantom to reproduce the behavior of iron overload in the liver by MRI and (ii) assessment of the variability of a previously validated method to quantify liver iron concentration between different MRI devices using the phantom and patients. Materials and Methods. A phantom reproducing the liver/muscle ratios of two patients with intermediate and high iron overload. Nine patients with different levels of iron overload were studied in 4 multivendor devices and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…5 Additionally, reproducibility of MRI-derived LIC estimates has been shown to be superior to that of biopsy measurements. [6][7][8][9] Understanding the potential limitations and performance of R2* quantitation for LIC estimation is valuable when implementing this diagnostic tool at large sites. and R2* are closely correlated with LIC using data acquired on a 1.5 T MRI system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Additionally, reproducibility of MRI-derived LIC estimates has been shown to be superior to that of biopsy measurements. [6][7][8][9] Understanding the potential limitations and performance of R2* quantitation for LIC estimation is valuable when implementing this diagnostic tool at large sites. and R2* are closely correlated with LIC using data acquired on a 1.5 T MRI system.…”
Section: Introductionmentioning
confidence: 99%
“…6 Alústiza et al found that a signal intensity ratio (SIR) method of calculating LIC is reproducible on several different 1.5 T systems. 7 Therefore, various studies have shown that MR image analysis can be used in conjunction with specified image acquisition techniques to estimate patient LIC. Furthermore, intramachine reproducibility of those measurements has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The material should be stable over a period of time and without signal interference [3]. Several transition metals were applied as paramagnetic contrast agents to prepare phantoms with desired T 1 and T 2 values such as nickel [4], gadolinium [3] and iron [5] compounds. Nevertheless, only one type of metal was developed as magnetic nanoparticle contrast agent, Ferumoxides-for MRI phantom [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only one type of metal was developed as magnetic nanoparticle contrast agent, Ferumoxides-for MRI phantom [6]. However, these particles lack the reliable stability due to the precipitation of irons at the bottom of the tubes in the phantom [5].…”
Section: Introductionmentioning
confidence: 99%